Computer aided method for 3D assessment of the lower limb alignment for orthopedic surgery planning - Ferreira, Tomás Augusto Esteves (2017)
Tese de mestrado integrado, Engenharia Biomédica e Biofísica (Engenharia Clínica e Instrumentação Médica) Universidade de Lisboa, Faculdade de Ciências, 2017